Marketing conditions of Sports Competition Business in Chiang Mai - Suriyo, Annapon (Academic Journal of Thailand National Sports University, 2018)
The purposesof this research were1) to study the strengths, weaknesses, opportunities and treats of sports competition business in Chiang Mai. 2) to study the marketing conditions of sports competition business in Chiang Mai 3) to study the marketing mix that influences the decision to utilize sports competition services in Chiang Mai. The research is qualitative and quantitative research. The research samples were those who involved in sports management business. The samples were used in 7 in-depth interviews, 7 subgroups, and 40 questionnaires. The instruments used in the research were interviews and questionnaires. The research was conducted by in-depth interviews. Specifically, and subgroup discussion. Analysis of data by in-depth interview by using the content analysis which got along with the collectionof data from the research objectives. The data were analyzed by frequency, percentage, mean, and standard deviation It was found that the market conditions of the sport management business in Chiang Mai provide more strengths than weaknesses and more opportunities than threats. Therefore,offensive business strategies can beemployed.Thesports competition business in Chiang Mai were found to be non-competitive. Most competitions have been organized by stadium owners or government agencies and participated by sports enthusiasts without any unique sporting events not identity of its province. The service users will have a lot of bargaining power, as sports event organizing business has aimed for organizing activities for the mass just to meet the objective and effectiveness of the event rather than profit. Entrant barriers for new comers are low, as no fixed assets investment is needed. Only skills and experiences in event management and alliances with related organizations are required. The owners of artificial turfs and golf courses imposed higher entrant barriers to new comers as much higher investment, fixed assets and land are required. The bargaining power of the raw material suppliers is low as sports event organizing business involve many parties and their collaboration. The threat of replacement product is low as sports event organizing business demands knowledge and experience of organizers. Possible threats are from internal self-organized sport events without outsourcing. Marketing factors influencing decision making at a high level are firstly personnel, secondly distribution and product.